PRODUKSI ANTIBODI KUNING TELUR (IgY) ANTI STREPTOCOCCUS MUTANS SEBAGAI ANTI KARIES GIGI - Okti Nadia Poetri; Retno D Soejoedono (Institut Pertanian Bogor, 2006)
The aim of this study was to explore IgY anti Streptococcus mutan production and the ability of Igy Streptococcus mutans blocking adhesion process. The eggs was collected from Single Comb Brown Leghorn which have been immunized by S. mutan. Agar gel precipitation test was done to detect IgY anti S. mutans in serum and egg. Egg which Countain IgY anti S. mutans was collected. IgY anti S. mutans extracted from egg yolk by mean s PEG-Amonium sulfat and purified using fast protein liquid chromatography. The purity of Igy anti S. mutans was determined by UV spectropometer. Biological activities of Igy anti S. mutans to inhibit adhession process was learned by anti adhesion test. We use two dose of IgY, which is 100 ug and 500 ug. Igy anti S. mutans formen in serum five weeks after the first immunization while it formed in egg nine weeks after the first immunization. Igy anti S. mutanss still present in serum andegg until twelve weeks from the first immunization. Igy anti S. mutanss could decrease the amount of bacteria which attach the epithelial cell surface. The amount of sticky bacteria on epithelial cell (without IgY) are 40 cell bacteria/epithelial cell. After blocked by IgY anti S. mutanss the amount of bacteria turn into 30 cell bacteria/epithelial cell (for dose of 100 ug IgY) and 28 cell bacteria/epitheelial cell (for dose of 500 ug IgY). This research concluded that hens were capable producing IgY anti S. mutanss in egg yolk and it can be used to solve dental caries problem which caused by S. mutanss.